p53 mutations are not selected for in simian virus 40 T-antigen-induced tumors from transgenic mice. - Moore, M (1992)
Many diverse tumors contain cells that select for mutations at the p53 gene locus. This appears to be the case because the p53 gene product can act as a negative regulator of cell division or a tumor suppressor. These mutations then eliminate this activity of the p53 gene product. The simian virus 40 (SV40) large T antigen binds to p53 and acts as an oncogene to promote cellular transformation and initiate tumors. If the binding of T antigen to the p53 protein inactivated its tumor suppressor activity, there would be no selection pressure for p53 mutants to appear in tumors. To test this idea, transgenic mice that carried and expressed the SV40 large T-antigen gene were created. Expression of the T antigen was directed to the liver, using the albumin promoter, and the choroid plexus, using the SV40 enhancer-promoter. A large number of papillomas (indicated in parentheses) of the choroid plexus (14), hepatocellular carcinomas (5), liver adenomas (10), and tumors of clear-cell foci (5) were examined for mutant and wild-type p53 genes and gene products. In all cases, the tumor extracts contained readily detectable T-antigen-p53 protein complexes. A monoclonal antibody specifically recognizing the wild-type p53 protein (PAb246) reacted with p53 in every tumor extract. A monoclonal antibody specifically recognizing mutant forms of the p53 protein (PAb240) failed to detect p53 antigens in these extracts. Finally, p53 partial cDNAs were sequenced across the regions of common mutations in this gene, and in every case only the wild-type sequence was detected. These results strongly support the hypothesis that T antigen inactivates the wild-type p53 tumor-suppressing activity and there is no need to select for mutations at the p53 locus.